2012
DOI: 10.1186/1479-5876-10-215
|View full text |Cite
|
Sign up to set email alerts
|

Abnormal expression of GADD45B in human colorectal carcinoma

Abstract: BackgroundGADD45B is a member of the growth arrest DNA damage-inducible gene family associated with cell growth control, apoptosis, and DNA damage repair response. The aim of this study is to detect the role of GADD45B in colorectal carcinoma (CRC); the area not studied in depth to date.MethodsThe mRNA and protein levels of GADD45B were examined by Real-Time quantitative PCR (RT-qPCR) and immunohistochemistry (IHC) in CRC tissues and adjacent noncancerous tissues (ANCT). Over-expression plasmids and SiRNA were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
36
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(36 citation statements)
references
References 38 publications
0
36
0
Order By: Relevance
“…In one study, point mutations were found in exon four of the Gadd45a gene in 14 % of pancreatic cancer samples, and Gadd45a expression in p53-positive tumors was associated with a lower patient survival rate. Gadd45b expression was associated with increased relapse and patient death in human colorectal carcinoma (Wang et al 2012 ) Gadd45a induction also protects melanoma cells from UV radiation-induced death. Lack of Gadd45a induction in cervical carcinomas correlates with a good clinical response to radiotherapy (Gao et al 2009 ).…”
Section: Involvement Of Gadd45 In Tumorigenesismentioning
confidence: 98%
“…In one study, point mutations were found in exon four of the Gadd45a gene in 14 % of pancreatic cancer samples, and Gadd45a expression in p53-positive tumors was associated with a lower patient survival rate. Gadd45b expression was associated with increased relapse and patient death in human colorectal carcinoma (Wang et al 2012 ) Gadd45a induction also protects melanoma cells from UV radiation-induced death. Lack of Gadd45a induction in cervical carcinomas correlates with a good clinical response to radiotherapy (Gao et al 2009 ).…”
Section: Involvement Of Gadd45 In Tumorigenesismentioning
confidence: 98%
“…A granular cytoplasmic stain was defined as positive. Briefly, the staining index (SI, range 0-9) was calculated as the result of the intensity score (0, no staining; 1 þ , faint/equivocal; 2 þ , moderate; 3 þ , strong) and the distribution score (0, no staining; 1 þ , staining of o10% of cells; 2 þ , between 10 and 50% of cells; and 3 þ , staining of 450% of cells) 52 . For tektin4 protein in this study, a moderate/strong cytoplasmic staining (SI ¼ 5-9) was defined as tektin4-high, while a weak or negative staining (SI ¼ 0-4) was defined as tektin4-low/normal 53,54 .…”
Section: Methodsmentioning
confidence: 99%
“…Functional enrichment analysis using IPA for the downregulated genes revealed that the 2 most significantly enriched pathways were hereditary breast cancer signaling ( P < 1.08 × 10 –4 ) and interleukin 2 signaling ( P < 6.84 × 10 –4 ), both of which were driven by oncogenes KRAS , IL‐2RB , and GADD45B (Fig. D) . For upregulated genes, the most significantly enriched pathway was nucleotide excision repair ( P < 1.54 × 10 –2 ), which was driven by the tumor suppressor gene ERCC1 (Fig.…”
Section: Resultsmentioning
confidence: 95%
“…1D). 28 For upregulated genes, the most significantly enriched pathway was nucleotide excision repair (P < 1.54 3 10 -2 ), which was driven by the tumor suppressor gene ERCC1 (Fig. 1D).…”
Section: Genes Significantly Associated With Soy Food Intakementioning
confidence: 97%